Moralische Gefühle als Grundlage einer wohlstandschaffenden Wettbewerbsordnung: ein neuer Ansatz zur Erforschung von Sozialkapital und seine Anwendung auf China - Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2009)
In his comprehensive critique of current economic approaches to social capital, Durlauf (2002) recommends a stronger reliance on methods of experimental economics and social psychology. This paper surveys different notions of social capital and submits an alternative conceptual approach based on the economics of identity (Akerlof and Kranton 2000), which is supplemented by recent interdisciplinary insights into the role of emotions in coordinating human interactions. I claim that this perspective goes back to Adam Smith and his Theory of Moral Sentiments. A new definition of social capital is proposed that puts shared framed emotions into the central place. I apply this new approach on China, especially with reference to the notion of guanxi (networks).
urn:nbn:de:101:1-2009021926
Keywords: A12; D03; 330; Social capital; Adam Smith; economics of identity; shared framed emotions; China